RETRACTION: Surgical Site Wound Infection, and Other Postoperative Problems After Coronary Artery Bypass Grafting in Subjects with Chronic Obstructive Pulmonary Disease: A Meta‐Analysis (International wound journal, 2025)
RETRACTION: J. Gao, H. Wang, X. Liu, X. Song, and X. Zhong, “Surgical Site Wound Infection, and Other Postoperative Problems After Coronary Artery Bypass Grafting in Subjects with Chronic Obstructive Pulmonary Disease: A Meta‐Analysis,” International Wound Journal 20, no. 2 (2023): 302–312, https://doi.org/10.1111/iwj.13877. The above article, published online on 07 July 2022, in Wiley Online Library (http://onlinelibrary.wiley.com/), has been retracted by agreement between the journal Editor in Chief, Professor Keith Harding; and John Wiley & Sons Ltd. Following an investigation by the publisher, all parties have concluded that this article was accepted solely on the basis of a compromised peer review process. The editors have therefore decided to retract the article. The authors did not respond to our notice regarding the retraction.